Perlindungan Hukum Bagi Koperasi Simpan Pinjam Dalam Penyelesaian Kredit Macet (Studi Lembaga Keuangan Mikro Dana Yaksa Mino Saroyo Kabupaten Cilacap) - Solahudin, Muhamad Sofyan; Attamimi, Zeehan Fuad (CV. Era Digital Nusantara, 2024)
The research focuses on the credit resolution mechanisms and legal protection efforts implemented to ensure the sustainability of cooperative operations. The method employed in this research is a mixed-methods approach, specifically a normative-empirical legal research method. The findings indicate that MFI Dana Yaksa adheres to credit agreements in line with operational management standards, guided by the principles of caution and sound lending practices. When dealing with loan defaults, a familial approach takes precedence, while collateral auctions are considered a last resort if salvage efforts are unsuccessful. This strategy ensures the efficient and responsible handling of credit, supporting the continuity of Savings and Loan Cooperative operations amidst the dynamics of the local economy.